Plans of the River St. Lawrence below Quebec sheet 6 from Seal Islands to Orleans Isle / surveyed by Captn. H.W. Bayfield 1827-1834 - Bayfield, Henry Wolsey, 1795-1885 (Great Britain. Hydrographic Office, 1848)
Decr. 1st 1837, Cord. to 1848. Chart no. 316. Shows soundings, depth curves, nature of bottoms, tidal information, lighthouses; relief by hachures and spot heights along shore with notes on nature of shoreline, mouths of rivers, etc.; place-names; notes on variation of compass; some sheets with coastal profiles, illustrations or views. Grayscale;